Effects of Exposure to Tobacco Cigarette, Electronic Cigarette and Heated Tobacco Product on Adipocyte Survival and Differentiation In Vitro - Zagoriti, Zoi; El Mubarak, Mohamed A.; Farsalinos, Konstantinos; Topouzis, Stavros (Toxics (Basel), 2020)
Cigarette smoking (CS) causes significant morbidity worldwide, attributed to the numerous toxicants generated by tobacco combustion. Electronic cigarettes (ECIG) and heated tobacco products (HTP) are considered alternative smoking/vaping products that deliver nicotine through an inhaled aerosol and emit fewer harmful constituents than CS. However, their long-term impacts on human health are not well established. Nicotine exposure has been linked to lipolysis and body weight loss, while smoking has been associated with insulin resistance and hyperinsulinemia. Enhanced function of beige (thermogenic) adipocytes has been proposed as a means to reduce obesity and metabolic disorders. In this study, we compared the effect of extract-enriched media via exposure of culture medium to CS, HTP aerosol, and ECIG aerosol on the viability and the differentiation of 3T3-L1 pre-adipocytes to beige adipocytes. Only CS extract caused a decrease in cell viability in a dose- and time-dependent manner. Furthermore, relative lipid accumulation and expression levels of the adipocyte markers Pgc-1α, Ppar-γ and Resistin were significantly decreased in cells exposed to CS extract. Our results demonstrate that CS extract, in contrast to HTP and ECIG extracts, significantly impairs differentiation of pre-adipocytes to beige adipocytes and may therefore impact significantly adipose tissue metabolic function.